Revalorization of Cinnamon Leaves via a Phenolic Compound Extraction Process: An Optimization Using Box–Behnken Design - José Arturo Olguín-Rojas; Laura Mayoris Aguilar-Veloz; Paulina Aguirre-Lara; Irving David Pérez-Landa; Cecilia Vazquez-Gonzalez; Manuel González-Pérez (Proceedings)
The cultivation of cinnamon (Cinnamomum zeylanicum) is one of the most important worldwide [...]